Ontology of doctor and patient relationship and bioethics: from Aristotle's teleology to Pellegrino's philosophy of medicine - Ferreira, Nuno Ribeiro (2024)
Some philosophical and metaethical theories have tried to provide a fundamental background for bioethics but miss the fundamental question about what medicine is, its nature and its end. We argue that the philosophy of medicine, through the development that Edmund Pellegrino and David Thomasma gave to this field of study, allied with Aristotle’s practical and teleological ethics, can provide an ontological background for bioethics beyond the tradition of principles and deontology, with particular emphasis on the uniqueness of the doctor-patient encounter. Some difficulties and criticisms of this ontological model are also examined.